The Fields of Britannia: Continuity and Discontinuity in the Pays and Regions of Roman Britain. (June 2013) - Rippon, Stephen; Smart, Chris; Pears, Ben; Fleming, Fiona
Abstract : Abstract : The transition from Roman Britain to medieval England and Wales clearly saw profound changes in society and landscape, with the large-scale abandonment of the settlements most closely associated with Romanitas – villas and towns – and the emergence of new architectural styles, burial rites, and other material culture of Germanic character. These changes in the archaeological record suggest profound social dislocation for the higher echelons of society, but have deflected attention away from what may have been a very different story for the majority of the rural population. This article offers a preliminary description of the results of the Fields of Britannia Project, which is examining the potential for continuity and discontinuity in agricultural landscapes across the different regions of Roman Britain. Three strands are explored: the palaeoenvironmental sequences that record how patterns of land use changed over time, the relationship between excavated Romano-British field systems and those of the medieval period, and the ways in which settlement patterns evolved. All three point to considerable potential continuity and a lack of evidence for large-scale post-Roman abandonment of the rural countryside in lowland areas.